مقصد إصلاح العالم في القرآن الكريم: Reform of the World Order as a Qur'anic Intent - Farida Hayed - حايد, فريدة (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2017)
يهدف البحث إلى بيان حقيقة الإصلاح وأسسه في القرآن الكريم بوصفه أهم المقاصد الشرعية وأعظمها؛ فالإصلاح -بما يعني من دفع للفساد، وإحلال للنفع- مقصد قطعي قرآني هدفه حفظ نظام العالم، واستدامة صلاحه بصلاح المهيمن عليه وهو الإنسان. وقد أشار البحث إلى أن أساس الإصلاح الإنساني هو إصلاح التفكير الذي يقود إلى إصلاح الأعمال التي لها أثرها في بناء الحضارة والعمران. This paper addresses the nature of reform and its foundations in the Gracious Qur'an, as reform is considered the most important and legitimate intent. Reform (Islah), i.,e. achieve the good and prevent corruption, is a definite Qur'anic intent, to preserve the World order and maintain its good quality through the good quality of Man, the vicegerent. The paper concludes that the basis of Man's reform is the reform of his thinking that leads to reform of his endeavor to build civilization and development.